Typology of irrigation systems in Ghana - Namara, Regassa E.; Horowitz, L.; Kolavalli, S.; Kranjac-Berisavljevic, Gordana; Dawuni, B.N.; Barry, Boubacar; Giordano, Mark (International Water Management Institute, 2010)
Interest in African irrigation investment is growing. However, irrigation is not a monolithic concept, and the opportunities and risks can vary substantially by approach. To help provide an understanding of the variation, this paper builds on previous work to provide a detailed typology of irrigation systems as currently used in Ghana.